The Influence of Financial Literacy, Consumptive Hebagior and Gender on the Financial Management of Generation Z on College Students in Surabaya City - Navillia Putri Salsabilah; Anik Yuliati (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
Financial management is a process of planning, organizing, directing, and controlling the use of financial resources effectively and efficiently to achieve certain financial goals. For generation Z students, the ability to manage finances is very important, especially amid the challenges of low financial literacy, high consumptive behavior, and gender differences. This study aims to examine the effect of financial literacy, consumptive behavior, and gender on student financial management. This study uses a quantitative approach with purposive sampling method. The population in this study was all students of public universities in the city of Surabaya with accounting study programs. The sample in this study consisted of 105 respondents who were active students majoring in accounting in the city of Surabaya. The data collection technique was carried out through distributing questionnaires online using Google Form. The data were analyzed using the Partial Least Squares (PLS) method. The results showed that financial literacy, consumptive behavior, and gender affect student financial management.